2022
DOI: 10.1038/s43247-022-00620-5
|View full text |Cite
|
Sign up to set email alerts
|

Present-day warm pool constrains future tropical precipitation

Abstract: Future changes in tropical precipitation affect the livelihood of the world’s human population and ecosystems. Climate models project an increased rainfall intensification under anthropogenic warming, but uncertainties in the distribution and magnitude of the changes remain large. Here, we identify a strong positive relationship between the present-day Indo-Pacific warm pool size and projected precipitation changes in the central-to-eastern tropical Pacific using multi-model simulations. Models with larger pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Despite the strong diversity among the SWG models, the precipitation sensitivity in the CP is enhanced with the increase in WPI in the PD climate, which may have contributed to the eastward shift of the convective zone under greenhouse warming. Thus, in addition to the warm pool size in PD climate (Park et al 2022b), our results suggest that the WPI is also an important factor for the model uncertainties in tropical precipitation projections. Therefore, aligning with other factors (i.e., IPWP size) more realistic simulations of the WPI in PD climate would be helpful to improve the credibility of the simulated projections.…”
Section: Summary and Discussionmentioning
confidence: 78%
“…Despite the strong diversity among the SWG models, the precipitation sensitivity in the CP is enhanced with the increase in WPI in the PD climate, which may have contributed to the eastward shift of the convective zone under greenhouse warming. Thus, in addition to the warm pool size in PD climate (Park et al 2022b), our results suggest that the WPI is also an important factor for the model uncertainties in tropical precipitation projections. Therefore, aligning with other factors (i.e., IPWP size) more realistic simulations of the WPI in PD climate would be helpful to improve the credibility of the simulated projections.…”
Section: Summary and Discussionmentioning
confidence: 78%
“…For the precipitation field, while there are many local impacts of the warm pool area bias in the Pacific (Park, Yeh, Min, Ham, & Kirtman, 2022), we will focus here on remote teleconnections into the extratropics and Atlantic. Models with a smaller warm pool tend to simulate more precipitation in the northwestern United States and southwestern Canada (gray box in Figure 2f) and more precipitation in northeastern South America and the tropical West Atlantic (red box in Figure 2f) (see also Figures S2c and S2d for scatter plots of all 40 models).…”
Section: Implications For the Subtropical Jet And Precipitation In Th...mentioning
confidence: 99%
“…Wang et al demonstrated that both CMIP5 and CMIP6 models simulate an excessively tilted thermocline, leading to excessive SST variability in the equatorial Indian Ocean (Wang et al, 2021). Previous studies have shown that simulate a larger warm pool area in the present day and predicted an excessive warming in the future in the eastern tropical Pacific due to intensified ocean stratification (Park et al, 2022). Liu et al showed that CMIP6 multi‐model mean reproduces the warm pool size well, but there is large spread among models, with models with smaller warm pool areas (larger biases) tending to simulate weaker WTP SST (Liu & Grise, 2023).…”
Section: Introductionmentioning
confidence: 99%